Efflux pump inhibitors for bacterial pathogens: From bench to bedside - Sharma, Atin (Indian J Med Res, 2019)
With the advent of antibiotics, bacterial infections were supposed to be a thing of past. However, this instead led to the selection and evolution of bacteria with mechanisms to counter the action of antibiotics. Antibiotic efflux is one of the major mechanisms, whereby bacteria pump out the antibiotics from their cellular interior to the external environment using special transporter proteins called efflux pumps. Inhibiting these pumps seems to be an attractive strategy at a time when novel antibiotic supplies are dwindling. Molecules capable of inhibiting these pumps, known as efflux pump inhibitors (EPIs), have been viewed as potential therapeutic agents that can rejuvenate the activity of antibiotics that are no longer effective against bacterial pathogens. EPIs follow some general mechanisms of efflux inhibition and are derived from various natural as well as synthetic sources. This review focuses on EPIs and identifies the challenges that have kept these futuristic therapeutics away from the commercial realm so far.